2019
DOI: 10.1159/000496068
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of Hematopoietic Stem Cells: Emerging Assays, Cryoprotectant Agents, and Technology to Improve Outcomes

Abstract: Hematopoietic stem cell (HSC) therapy is widely used to treat a growing number of hematological and non-hematological diseases. Cryopreservation of HSCs allows for cells to be transported from the site of processing to the site of clinical use, creates a larger window of time in which cells can be administered to patients, and allows sufficient time for quality control and regulatory testing. Currently, HSCs and other cell therapies conform to the same cryopreservation techniques as cells used for research pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 87 publications
2
63
0
Order By: Relevance
“…Any potentially cytotoxic effects of cryoprotectants, especially DMSO, will be reduced by lowered temperature and the avoidance of abrupt temperature change. Consequently, working temperatures in the range 0–4°C are beneficial ( 15 , 73 , 75 ) and practices such as adding cooled protectant to precooled cells or warmer protectant to warmer cells with immediate subsequent cooling are to be recommended ( 114 116 ).…”
Section: The Freezing Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Any potentially cytotoxic effects of cryoprotectants, especially DMSO, will be reduced by lowered temperature and the avoidance of abrupt temperature change. Consequently, working temperatures in the range 0–4°C are beneficial ( 15 , 73 , 75 ) and practices such as adding cooled protectant to precooled cells or warmer protectant to warmer cells with immediate subsequent cooling are to be recommended ( 114 116 ).…”
Section: The Freezing Processmentioning
confidence: 99%
“…Sample volume reduction, achieved by increasing cell concentration, can be attractive as it will limit materials and reagents used, processing time and cryostorage space as well as reducing the quantity of DMSO infused to the patient ( 11 , 117 119 ). However, cell concentrations higher than ~200 × 10 6 cells/mL appear detrimental on engraftment prediction (through the CFU-GM assay) or engraftment yield post-thaw ( 88 , 114 , 117 , 118 , 120 , 121 ). As the ice fraction within a cooling sample grows and the unfrozen channels, where cells are confined, reduce in size there will be an increase in potentially injurious compression forces and direct cell to cell contact ( 11 ).…”
Section: The Freezing Processmentioning
confidence: 99%
“…In addition, the automated system should allow process controls for temperature and the rate of cryoprotectant addition. Reiterating the point, the addition of cryoprotectant such as DMSO, to a cell suspension is an exothermic reaction and the release of energy could damage the cells [6,12]. Considering this significant need for process controls and slow addition of pre-cooled cryoprotectant, an automated system must provide controlled-rate addition of cryoprotectant and should monitor the temperature throughout the formulation and fill process.…”
Section: Considerations For a Functionally Closed Automated Systemmentioning
confidence: 99%
“…Dimethyl sulfoxide (Me 2 SO) is the most widely used cryoprotectant for cell therapy [12]; however, it is known to induce toxicity and epigenetic changes in cells [13,14]. Also, numerous studies have reported Me 2 SO-related adverse reactions following infusion of Me 2 SO-preserved cell products, ranging from mild events such as nausea, vomiting, headache, hypotension, hypertension and diarrhea to severe reactions such as cardiac arrhythmias, cardiac arrest, respiratory stress and epileptic seizures [5,11,13,15,16]. Thus, it would be desirable to reduce the levels of Me 2 SO (e.g., from 10% to 5% [17,18]) in cellular products for clinical use both in final and intermediate products.…”
Section: Introductionmentioning
confidence: 99%
“…Developing new optimized protocols, vials and devices that improve cell cryopreservation/thawing and allow standardization could increase the cellular recovery and functionality of cryopreserved cells, ensuring their effective clinical application, ultimately benefiting the patient [29]. Although considerable progress has been made in optimizing freezing protocols, freezing media composition, cooling devices and cryovials to ensure that cell products are safe and retain their therapeutic characteristics following cryopreservation, more research focused on improving cell recovery and Me 2 SO-associated injury is still needed [5,11].…”
Section: Introductionmentioning
confidence: 99%